2021
DOI: 10.1097/anc.0000000000000805
|View full text |Cite
|
Sign up to set email alerts
|

A Multisite Survey of NICU Healthcare Professionals' Perceptions About Family-Centered Care

Abstract: Background: Family-centered care contributes to improved outcomes for preterm and ill infants. Little is known about the perceptions of neonatal intensive care unit (NICU) healthcare professionals regarding the degree to which their NICU practices or values family-centered care. Purpose: The aims of this study were to describe attitudes and beliefs of NICU healthcare professionals about family-centered care and to explore professional characteristics th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…The data from our study suggest athletic trainers feel they are practicing FCC, with the exception of “developmental needs.” However, there were significant differences between their practices and perceptions of FCC. These findings are consistent with previous studies conducted across other healthcare settings, such as nursing and neonatal intensive care units [ 14 , 18 , 19 ]. In addition, research has assessed the attitudes toward FCC among physical therapists, professionals with similar skill sets as athletic trainers, in the United States [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The data from our study suggest athletic trainers feel they are practicing FCC, with the exception of “developmental needs.” However, there were significant differences between their practices and perceptions of FCC. These findings are consistent with previous studies conducted across other healthcare settings, such as nursing and neonatal intensive care units [ 14 , 18 , 19 ]. In addition, research has assessed the attitudes toward FCC among physical therapists, professionals with similar skill sets as athletic trainers, in the United States [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…Athletic trainers reported parent-to-parent support as the highest perceived and most frequently practiced element of FCC. Interestingly, this element is not ranked highly across other healthcare professions for both perception and practice [ 18 , 19 , 25 , 26 , 27 , 28 , 29 , 30 ]. Athletic trainers reported practicing parent-to-parent support (mean = 3.93 ± 0.85) more frequently as compared to other professions, with mean scores ranging from 2.38 to 3.55 [ 18 , 19 , 26 , 28 , 29 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, this was a secondary analysis of text data gathered as part of a larger survey of family-centered current and necessary practices. 12 Therefore, there was no opportunity to follow up with respondents to clarify or explore comments in greater depth. Second, all sites reported providing family-centered care and the survey findings indicated that respondents overall highly rated their unit's current practice of familycentered care.…”
Section: Discussionmentioning
confidence: 99%
“…It is essential for NICUs to conduct their own assessments of their family-centered care practices, including strengths, weaknesses, resources, and gaps so that local solutions can be developed in partnership with family advisors. 12 Many resources are available to support family-centered quality improvement initiatives. 24,25 In summary, NICU healthcare professionals identified a range of issues that impede delivery of family-centered care and provided actionable recommendations for improvement.…”
Section: What We Can Do Todaymentioning
confidence: 99%